The Influence of Information Quality and Perceived Value on Purchase Intention of Game shop E-commerce in Generation Z Based on Framing Theory - Gusti Muhammad Farhan; Endy Gunanto Marsasi (LPPM Universitas Trunojoyo Madura, 2023)
Indonesia's gaming sector is expanding quickly in this day and age, which has an effect on the country's digital market economy. One aspect of Indonesia's expanding gaming sector is online game shops. The purpose of this study was to determine the effect of information quality, social psychological distance, perceived value, and trust on Generation Z customers' purchase intentions in game shop e-commerce. This study uses a quantitative approach by distributing questionnaires. With 260 samples overall, non-probability sampling is the approach used. Structural Equation Modeling (SEM) utilizing AMOS 26 Graphics software is the analytical technique used. The overall conclusions of the study are that social psychological distance has a positive, significant impact on trust and also acts as a mediator between the effects of information quality and trust. Information quality has a significant positive impact on social psychological distance. Information quality influences perceived trust and value in a significant positive way. Identified purchase intention is positively and significantly influenced by trust and perceived value. Trust and perceived value also act as mediators between information quality and purchase intention. The benefits of this research is reported managers of game shop e-commerce companies must increase the development of companies that distribute information with a high level of information quality. In addition, trust in customers and purchase intention impacted readily by the social psychological distance between business people and consumers and how much value consumers feel for the goods and services played by business people.